(untitled) (AOQU (Achilles Orlando Quixote Ulysses). Journal on Epic, 2022)
The most relevant work of the literary Baroque in the Romanian language is the mock-heroic poem in twelve cantos, in decasyllabic six-line stanzas, Țiganiada (or The Gypsy camp), which Ion Budai-Deleanu (1760-1820) wrote approximately between 1790-1812. Thanks to the wide use of the repertory of possible different forms of intertextuality, the poem Țiganiada can nowadays be considered as one of the best illustrations of the «literature de second degré» Gerard Genette speaks of. The self-comment Budai-Deleanu abundantly places in the footnotes must therefore be read and considered as an integral part of the poem: it becomes a sort of «philological comedy» (Nicolae Manolescu), where the various fictitious characters of the commentators, with their allusively eloquent names, interact, often on a burlesque level.